(untitled) (Manila, 2011)
Contents: The core environment program (CEP-BCI); Environmental assessments of economic corridors and sectors; Biodiversity conservation corridors intiative (BCI)...
Keywords: Biodiversity conservation,Bảo tồn đa dạng sinh học